Correlation Between Macular Microstructural Changes with Disease Staging and Visual Acuity in Diabetic Retinopathy - Zhang W; Zhang F; Yang Y; Cao J; Zhu Z (International Journal of General Medicine, 2025)
Wenhua Zhang, Feng Zhang, Yezhen Yang, Jiamin Cao, Ziyi Zhu Department of Ophthalmology, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People’s Republic of ChinaCorrespondence: Ziyi Zhu, Department of Ophthalmology, The Third Xiangya Hospital, Central South University, Changsha, Hunan, 410013, People’s Republic of China, Email 570104073@qq.comPurpose: To investigate the changes in macular microvascular structure at different stages of diabetic retinopathy (DR) and the correlation between macular ischemia and visual acuity.Patients and Methods: A prospective cross-sectional study was conducted. A total of 173 patients with DR were enrolled and divided into three groups according to DR stage. The control group consisted of 29 gender and age matched healthy individuals. Macular perfusion indexes were measured by optical coherence tomography angiography (OCTA) and compared.Results: The p-values of central foveal thickness (CFT), focal avascular zone (FAZ) area, and vessel density were less than 0.05 in DR patients and healthy individuals. As the severity of DR increased, there was a corresponding decline in visual acuity, the logMAR best corrected visual acuity (BCVA) was 0.40± 0.30 in mild-moderate NPDR, then worsened to 0.48 ± 0.30 (p=0.059) in severe NPDR and further to 0.60 ± 0.34 (p=0.043) in PDR. Superficial capillary plexus (SCP) vessel density correlated negatively with logMAR BCVA (p< 0.001, R=− 0.267), whereas the severity of DR correlated positively with logMAR BCVA (p< 0.001, R=0.199). And increased DR stage was associated with significant reductions in foveal density at 300 μm (FD-300 μm; p=0.004) and deep capillary plexus (DCP) vessel density (p=0.009).Conclusion: Macular perfusion status decreases as DR progresses. Early changes of macular microvascular structure in different capillary plexus may indicate progression of DR severity and affect visual acuity.Keywords: diabetic retinopathy, macular perfusion status, visual acuity, OCT angiography